Understanding the role of khalifa for the foundation of wizard khalifa tourism - Mohd Any, Azrul Anaz; Ahmat, Norunnajah; Robani, Anidah; Fam, Soo Fen; Abas, Siti Aisah; Saad, Mazni (2019)
—Branding has helped Malaysian tourism industry moving forward in this highly competitive world. Till now these Malaysian brands such as Malaysia Truly Asia or Muslim friendly country or Halal-friendly country are still relevant but a new perspective toward Malaysia is a need. Thus, this research aimed to offer a new the approach of tourism branding that would put Malaysian in the map of the world again. This new approach of branding is a concept of Wizard Khalifa Tourism (WKT). It was introduced to relook philosophically at the role of mankind that man is not a lord on earth but merely as a tourist in this world. In order to be the wizard Khalifa tourist, he or she must return to the purpose of man’s creation on earth, as demanded by Allah; the role of Khalifa or a vicegerent man. Then, when men have retrieved the understanding of the purpose of their existence in this world; later, they would act to benefit other helixes in this world in general and in the world of tourism, in specific aspect